Social Stigma as a Predictor of Academic Help-Seeking Behavior: Evidence from Indonesian College Students - Indra Prapto Nugroho; Muhammad Shodikul Haq; Ria Thalia (Kuras Institute, 2025)
High academic pressure, social expectations, and performance demands make students vulnerable to psychological disorders. Although seeking academic help is an important adaptive strategy, many students refrain from doing so for fear of being perceived as weak or incompetent. Previous research has focused more on stress factors, literacy, and personality, while the role of social stigma as a direct determinant of academic help-seeking behavior has not been widely explored, especially in the Indonesian cultural context. Therefore, this study aims to determine how social stigma affects academic help-seeking in college students. The research sample was purposive sampling, resulting in 303 participants (53 males and 250 females) who were active students in Sumatera, Java, and Kalimantan, Indonesia, with experiences of unpleasant social stigma. Data collection techniques used the Academic Help-Seeking Scale (AHSS) and the Public Stigma Scale (PSS). Data analysis techniques using quantitative methods with simple regression. The results showed that, simultaneously, public stigma is a predictor and contributes to academic help-seeking.